The urethra of healthy female dogs can be normally narrowed due to the urethral flexure in retrograde CT urethrography. Issue 1 (25th November 2020) - Kang, Kyuyong; Kim, Kyeonga; So, Jaebeom; Lee, Jieun; Jang, Yongseok; Choi, Jeongwoo; Choi, Mincheol; Yoon, Junghee
Abstract: Quantitative analysis of urethral size in male dogs by retrograde CT urethrography using a power injector is a recently reported technique. The aim of the current, prospective, analytical study was to apply the same method to six, healthy, intact female Beagle dogs. The proximal ( P < .0001) and middle ( P = .0010) urethral volumes significantly differed between the empty and distended bladder states, although no significant difference was observed in the distal volume ( P = .0971). Unlike male dogs, female dogs showed two patterns of the urethral course: a straight urethra and urethral flexure. The urethral flexure was always related to intrapelvic position of the urinary bladder, and the more caudal the location of the vesicourethral junction beyond the pecten of the pubic bone, the more marked the appearance of the urethral flexure. Analysis of the urethral diameter at five sites (adopted from the previous radiographic study) was performed, and the urethral diameter showed a significant difference between the empty and the distended bladder states at sites 1 (vesicourethral junction, P < .0001), 2 ( P < .0001), and 3 ( P = .0244). However, there were no significant differences at sites 4 ( P = .2516) and 5 (inflatable retention bulb, P = .1260). The urinary bladder may be in part intrapelvically located in clinically healthy female dogs, and urethral flexure and urethral narrowing can result from the intrapelvic location of the bladder. Narrowing of the urethra should be interpreted with caution when the pelvic bladder is identified.